INDEKS OVERLAP DAN SINKRONISASI PEMBUNGAAN DALAM KEBUN BENIH KAYUPUTIH (Melaleuca cajuputi) DI PALIYAN, GUNUNGKIDUL - Noor Khomsah Kartikawati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2015)
Flowering synchrony will support the extent of random mating among families and hence the genetic gain in the resultant progeny. In the study, synchrony among families for flowering and peak flowering was estimated through the phenogram as well as the overlapping index. Research was carried out at cajuput (Melaleuca cajuputi sub species cajuputi) seed orchard in two flowering periods (2010 and 2011) at Paliyan, Gunungkidul. The observation results showed that peak flowering occurred in the middle of January and more than 75% families in cajuput seed orchard have the same flowering time. More than 90% families have overlapping index value greater than 0.8 in contrast to 2 families originated from Western and Northern Australia which revealed very low (<0.6) overlapping index. Seeds harvested from the cajuput seed orchard showed high genetic potencial, as 75% trees in Paliyan seed orchard produced seeds simultaneusly.